2019
DOI: 10.1088/1742-6596/1378/4/042105
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Use of Waste Polyethylene Terephthalate (PET) and River Sand in Roof Tile Production

Abstract: This study deals with the effects of using Polyethylene Terephthalate (PET) and river sand in roof tile production. This work is based on experimental study of roof tiles produced with river sand and recycled PET in varying proportion of 10%, 20%, 30%, 40%, 50%, 60% and 100% of PET combined with the corresponding fine aggregate percentage. The PET plastics used were derived from waste plastic bottles for soft drinks. The shredded plastic was subjected to heat and ensured that it does not lose it’s plasticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…This means that the water absorption of PET wall tiles is directly proportional to their PET content but inversely proportional to their POFA content. The water absorption efficiency of these polymer tiles is 75% lower than the concrete or ceramic tile and the result is similar to Bamigboye [25] observation. He noticed a gradual drop in water absorption values down to 100 percent PET, with 20-100 percent of PET falling within the standard's 2% range.…”
Section: Water Absorptionsupporting
confidence: 84%
See 2 more Smart Citations
“…This means that the water absorption of PET wall tiles is directly proportional to their PET content but inversely proportional to their POFA content. The water absorption efficiency of these polymer tiles is 75% lower than the concrete or ceramic tile and the result is similar to Bamigboye [25] observation. He noticed a gradual drop in water absorption values down to 100 percent PET, with 20-100 percent of PET falling within the standard's 2% range.…”
Section: Water Absorptionsupporting
confidence: 84%
“…Increases in PET material, on the other hand, decreased the density of the PET wall tile. Notably, as previously mentioned, the increase in PET content has decreased the density of the resulting composites [25,26].…”
Section: Densitymentioning
confidence: 53%
See 1 more Smart Citation
“…Production of plastic containers from pellets is a quicker and much cheaper process compared to the recycling and reuse processes this brings about a continuous increase in the generation of PET (Hopewell et al, 2009;Thompson et al, 2009). The rising-rate at which these plastic wastes are disposed cause negative impacts such as visual pollution, flooding, endangerment of sea animals, and wildlife (Maharaj et al, 2019;Bamigboye et al, 2019) PET has also made grave economic impacts. A report by Weber and Kroll (2019) states that plastic waste results in damages to the marine ecosystem worth US$13 billion annually.…”
Section: Polyethylene Terephthalate (Pet) Plastic Bottlesmentioning
confidence: 99%
“…The results of this investigation revealed that the physical and mechanical properties of roof tiles have good mechanical properties. It may conclude that, the use of discarded bottles for composite manufacturing is worthwhile, and it may assist to reduce environmental difficulties caused by PET bottles [37].…”
Section: Figure 1 -(A) Coconut Tree (B) Coconut Huskmentioning
confidence: 99%